Corporate Governance in Detecting Lack of Financial Report - Syamsudin, Syamsudin; Imronudin, Imronudin; Utomo, Sasongko Tri; Praswati, Aflit Nuryulia (JDM (Jurnal Dinamika Manajemen), 2017)
Fraudulent financial statements begins with the act of manipulating the financial statements for personal gain. Efforts to fulfill obligations on the rights of stakeholders make corporate governance play an important role in minimizing the occurrence of fraudulent financial statements. This study aims to investigate the phenomenon of corporate governance in detecting fraud or irregularities in the preparation of financial statements. Fraud detection is measured by the Beneish model.. The sample used in this research is 694 with manufacturing company period 2011-2015. Sampling technique with purposive sampling method. To test the Hypothesis used logistic regression analysis with moderation model. The results obtained are foreign ownership, domestic ownership and public ownership significant negative effect on fraud financial statement. While firm size has a significant positive effect fraud financial statement. Firm size as a moderating variable further strengthens the relationship between foreign ownership, domestic ownership and public ownership of fraud financial statements.